Reduced Use of Restricted and Danger-Labeled Pesticides in Florida Bell Pepper Production (1992-2004) - Mark A. Mossler (EDIS, 2005)
Pesticide use values for 2004 compared to peak usage data for the period 1992 through 2004 demonstrate a 56% reduction in the application of restricted or “Danger”-labeled insecticides in bell pepper. Paraquat use was reduced by 89%. Fumigant use (35% reduction) was mainly influenced by rate reduction, rather than reduction of use (1-7).  This document is PI-86, one of a series of publications of the Pesticide Information Office, Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2005.